An assessment of new technical of courses required by industries in Johor - Md. Rasli, Amran (Penerbit UTM Press, 1992)
Almost 3,000 skilled workers are produced by various skills training institutions, polytechnics, technical schools and vocational schools in Johor. Twenty Percent of these 'skilled workers' are actually trained dressmakers and beauticians - skill which are relevant to the manufacturing industry. Out of the remaining 2,400 skilled workers, 20 percent would opt to works in other states except Johor; and overseas especially Singapore, Japan and Taiwan. On the other hand, there is need for 30,000 skilled and semi-skilled workers to match the industrial sectors' demands. The shortage of skilled workers is made worse by the mismatch of skill produced and industrial demand, as well as inappropriate training programmes employed by government-sponsored technical training institutions. A survey was conducted in mid-1991 to assess the requirements of the manufacturing industry which are capital intensive and technological oriented based on then 'new' technical courses: Tool and Die, Basic, Electronics, Instrumentation (flow process), Pipe and High Pressure Welding, Chemical Technofogy, Mechanical Draughting With CAD, Surface Mounting Technology, Non-Destructive Testing, Rigging and Scaffolding, and High Precision Laser Cutting. This paper describes the process undertaken in conducting an industrial curvey and the interpretation of the analysis based on the findings of the findings of the study. The outcome of the survey which is presented in the final sections of this paper, should provide important data and insights for policy makers in reviewing the future need and form of technical training for technicians.